CP-120 Medication reconciliation in hospitals. (25th February 2017) - Darbon, F; Atkinson, S; Bourassa, E; Bédard, P; Bussières, JF
Abstract : Background: Medication reconciliation (MR) is a required organisational practice by accreditation and should be implemented in all hospitals. There are numerous issues reported with the implementation of MR. Purpose: The main objective was to survey the current MR practices in hospitals Material and methods: This was a descriptive cross sectional study conducted between May and June 2016. A survey of 34 questions was sent by email to all hospital pharmacy directors. The survey was managed online (SurveyMonkey, Palo Alto, CA, USA). Respondents were asked to share their policies, procedures and forms. Only descriptive statistics were performed. Results: 28 respondents (45 sites) completed the survey (response rate 82%). There was someone in charge of MR in 68% (30/44) of sites but only 43% (19/44) had a committee. The best possible medication history (BPMH) was always or often collected by pharmacy technicians (53%), pharmacists (51%), nurses (16%) or physicians/residents (7%). A second source of information was used systematically in 42% of cases (eg, patient drug profile (33/45), Quebec electronic health record (10/45), patient personal list (5/45), labels/bottles (3/45)). The BPMH was sometimes collected electronically (36%, 16/45). The BPMH (paper/electronic) was also used to prescribe drugs (47%, 21/45). Discrepancies were identified always or often by pharmacists (73%, 32/44), pharmacy technicians (39%, 17/44), physicians/residents (9%, 4/44) and nurses (2%, 1/44). Re-prescription was always/often done by physicians (65%, 26/40) and pharmacists (65%, 26/40). Only 29% (13/45) of the sites confirmed the consultation of the BPMH by the physician. Half of the sites (49%, 22/45) required the consultation of the BPMH before drug ordering at patient discharge. Pharmacists were involved in supervising discharge drug orders in 60% (26/44) of cases. A minority of respondents (27%, 12/45) gave additional material to patients at discharge. A majority (93%, 42/45) had contacts with community pharmacists whenever required to ensure seamless care. Staff involved in MR required inhouse certification (43%, 18/42) but almost all (91%, 39/43) provided tools to their staff to support the MR process. Conclusion: This cross sectional study revealed a need to standardise the MR process. No conflict of interest